O conector daí na língua escrita: uma abordagem modular - Cleidiene Novais Ferreira (2010)
This research aims the discursive role study of the connector daí. Thehypothesis considered in this study is the possibility of this item performs as a connector that relates textual constituents and discursive memoryinformation in the speech connection and organization. Focusing on its use in opinion articles, the way it performs under the Modular Analysis Model was investigated. To describe and investigate the discursive functioning of this item, the hierarchical, lexical and syntactic modules and the form of relational organization were approached. We believe that, throughout this analysis, conditions to describe and understand the perform of the item daí as a speech connector are created.